Early cephalometric characteristics in Class III malocclusion - Vanessa Costa Farias; Ricardo de Souza Tesch; Odilon Victor Porto Denardin; Weber Ursi (Dental Press Editora, 2012)
OBJECTIVE: Early identification of craniofacial morphological characteristics allows orthopedic segmented interventions to attenuate dentoskeletal discrepancies, which may be partially disguised by natural dental compensation. To investigate the morphological characteristics of Brazilian children with Class III malocclusion, in stages I and II of cervical vertebrae maturation and compare them with the characteristics of Class I control patients. METHODS: Pre-orthodontic treatment records of 20 patients with Class III malocclusion and 20 control Class I patients, matched by the same skeletal maturity index and sex, were selected. The craniofacial structures and their relationships were divided into different categories for analysis. Angular and linear measures were adopted from the analyses previously described by Downs, Jarabak, Jacobson and McNamara. The differences found between the groups of Class III patients and Class I control group, both subdivided according to the stage of cervical vertebrae maturation (I or II), were assessed by analysis of variance (ANOVA), complemented by Bonferroni's multiple mean comparisons test. RESULTS: The analysis of variance showed statistically significant differences in the different studied groups, between the mean values found for some angular (SNA, SNB, ANB) and linear variables (Co - Gn, N - Perp Pog, Go - Me, Wits, S - Go, Ar - Go). CONCLUSION: Assessed children displaying Class III malocclusion show normal anterior base of skull and maxilla, and anterior positioning of the mandible partially related to increased posterior facial height with consequent mandibular counterclockwise rotation.